ANALYSIS OF VIOLENCE IN CITY OF GOD FILM DIRECTED BY FERNANDO MEIRELLES - Simanjuntak, Marudut Bernadtua; Barus, Irma Rasita Gloria; Resmayasari, Ira (Study Program of English Literature, 2021)
Fernando Meireles'